Influence of automotive emission on air pollution using GIS in Faisalabad, Pakistan - Niaz, Yasir; Jiti, Zhou; Zhang, Yu (International Journal of Agricultural and Biological Engineering, 2015)
This study was conducted to explore the major sources of pollutants including total suspended particles and levels of NOx, COx, and SOx in Faisalabad Pakistan, which make key contributions to the smog in Faisalabad. Faisalabad is the third largest city of Pakistan where the situation is aggravating due to industrial expansion, population growth and an increasing volume of traffic. Study was conducted for the period of three months at different stations in Faisalabad. The concentrations of total suspended particles, levels of NOx, SOx and COx are 160 µg/m3 to 506 µg/m3, 26 µg/m3 to 64 µg/m3, 110 µg/m3 to 139 µg/m3 and 5.5 mg/m3 to 18.2 mg/m3 , respectively. As a result, air pollution control should not simply focus on controlling particulate emission, but also involve adopting an integrated multi-pollutant control strategy. Measured concentrations were at an intermediate level with respect to parameters by using Geographical Information System (GIS) and GPS. The results were compared with the permissible limits of United States Environmental Protection Agency (USEPA) and National Environmental Quality Standards (NEQS).DOI: 10.3965/j.ijabe.20150801.015Citation: Niaz Y, Zhou J T, Yu Z. Influence of automotive emission on air pollution using GIS in Faisalabad, Pakistan. Int J Agric & Biol Eng, 2015; 8(1): 111－116.